2021
DOI: 10.3389/fcell.2021.704341
|View full text |Cite
|
Sign up to set email alerts
|

NAT10-Mediated N4-Acetylcytidine of RNA Contributes to Post-transcriptional Regulation of Mouse Oocyte Maturation in vitro

Abstract: N4-acetylcytidine (ac4C), a newly identified epigenetic modification within mRNA, has been characterized as a crucial regulator of mRNA stability and translation efficiency. However, the role of ac4C during oocyte maturation, the process mainly controlled via post-transcriptional mechanisms, has not been explored. N-acetyltransferase 10 (NAT10) is the only known enzyme responsible for ac4C production in mammals and ac4C-binding proteins have not been reported yet. In this study, we have documented decreasing t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 43 publications
0
13
0
Order By: Relevance
“…We have previously reported that NAT10 depletion resulted in retarded meiotic progression in mouse oocytes, and NAT10mediated ac4C modification was a crucial regulator during oocyte maturation (20). In the current study, we knocked down NAT10 in GV stage mouse oocytes and performed transcriptome analysis to further identify the regulated genes and investigated the underlying mechanisms.…”
Section: Expression Profiling Of Nat10-depleted Mouse Oocytesmentioning
confidence: 85%
See 3 more Smart Citations
“…We have previously reported that NAT10 depletion resulted in retarded meiotic progression in mouse oocytes, and NAT10mediated ac4C modification was a crucial regulator during oocyte maturation (20). In the current study, we knocked down NAT10 in GV stage mouse oocytes and performed transcriptome analysis to further identify the regulated genes and investigated the underlying mechanisms.…”
Section: Expression Profiling Of Nat10-depleted Mouse Oocytesmentioning
confidence: 85%
“…The purpose of this study is to explore the important downstream genes and mechanisms of NAT10-mediated ac4C modification during oocyte maturation. In a previous study, we found that ac4C downregulation after NAT10 KD inhibited oocyte maturation, but the underlying mechanisms remained unknown (20). To further explore the underlying mechanisms, we conducted a transcriptomic study on oocytes with NAT10 KD and analyzed it with ac4C RIP data jointly (28).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Hutchinson-Gilford progeria syndrome (HGPS) 47 , epithelial ovarian cancer 48 , breast cancer 16 , and spermatogenesis 19 , and is most recently implicated in oocyte in vitro maturation (IVM) 49 . Mature oocytes are specialized, transcriptionally inert cells that almost exclusively contribute to the cytoplasm of zygotes when fertilized by sperm.…”
Section: Dysregulated Expression Of Nat10 Has Been Recently Linked To...mentioning
confidence: 99%